Integrasi Literasi Dan Projek Penguatan Profil Pelajar Pancasila Dalam Kurikulum PAI Di SMK Negeri 1 Sangatta Utara - Fatrah; Liana, Rosa; Anjani Putri Belawati Pandiangan (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
Merdeka Curriculum with its various intracurricular learning aims to optimise learners' learning process, strengthening their concepts and competencies. One of its important programmes is the Pancasila Learner Profile Strengthening Project (P5) which instils Pancasila values in everyday life. The Pancasila Learner Profile Strengthening Project encourages learners to learn actively and creatively, and develop a range of essential skills for the future. The implementation of literacy in students' reading and writing interests is the key to the success of the Pancasila Learner Profile Strengthening Project. The purpose of this research is to find out the integration of literacy and the Pancasila Learner Profile Strengthening Project (P5) in the PAI curriculum which will be carried out research in one of the vocational high schools (SMK), namely, at the SMK Negeri 1 Sangatta Utara school. This research uses qualitative research method with descriptive form. The results of this study indicate that the integration between literacy and the Pancasila Student Profile Strengthening Project (P5) in the Islamic Religious Education (PAI) curriculum has shown a very significant impact. The implementation of the integration of literacy and Pancasila profile cannot be separated from challenges. One of the main challenges is the limited wifi access in schools, which hinders the use of technology in learning. The solution is that the school tries to expand wifi access in the library or provide alternatives to using students' personal internet data. In addition, the role of the Islamic Religious Education teacher as a guide and supporter of this integration is very important